Residual stress assessment of nickel-based alloy 690 welding parts. (August 2015) - Lee, Sang-Hwan; Chang, Yoon-Suk; Kim, Sung-Woo
Highlights: We verified a FE analysis method for dissimilar metal welding simulation. The method was applied to a cylindrical weld block and CRDM penetration nozzles. The residual stress values were dependent on the inclination angle and welded zone. The analysis results were coincide with the crack locations found in a power plant. Abstract: Failures of welding parts in nuclear power plants have increased significantly. One of main degradation mechanisms was initiation and growth of primary water stress corrosion cracking accelerated by residual stress at dissimilar metal welds of piping, reactor head penetrations and nozzles connecting major components. Therefore, estimation of the welding residual stress became an important issue for ensuring reliability of them. The present study deals with verification of welding simulation techniques through sensitivity analyses of bottom-mounted instrumentation nozzle mock-up and control rod drive mechanism (CRDM) nozzle mock-up, examination of residual stress effects for a welded cylindrical block and application of the residual stress evaluation method to real penetration nozzles of CRDM made of nickel-based alloy 690.